Moderating effect of procedural justice in the relationship between participation in pay systems and personal outcomes - Ismail, Azman; Abdul Rahman, Hayazi; Wan Ismail, Wan Khairuzzaman (Faculty of Management and Human Resource Developemant, 2007)

(untitled)
This study examines the moderating role of procedural justice in the relationship between participation in pay systems and personal outcomes. This relationship was measured using 203 usable questionnaires that were gathered from hotel employees in Kuching, Sarawak. Outcomes of tests moderating model using hierarchical regression analyses showed that the inclusion of procedural justice into analysis had increased the effect of participation in pay systems on job commitment, but procedural justice had not increased the effect of participation in pay systems on job satisfaction. This result demonstrates that procedural justice does act as a partial moderator in the pay system models of the hotel industry sector. These findings have partially supported compensation studies conducted in most Western countries. In addition, the implications of this study to theory and practice, methodological and conceptual limitations, as well as directions for future research are elaborated in this paper.